Assessment of functional preparedness of athletes specializing in the sprint, using new methodological approaches - Маліков, Микола Васильович; Караулова, Світлана Іванівна (Slobozhanskyi Herald of Science and Sport, 2016)
Malikov N., Karaulova S. Purpose: study the character of the changes the level of functional preparedness of sportsmen in the autumn-winter preparatory period training cycle of one year. Material & Methods: in the study to take part ten of athletes specializing in the sprint at the age of 19–23 years, and which have sports rank master of Sport and international master of sports. Methods: analysis scientific and methodical literature, pedagogical supervision, pedagogical experiment, methods for assessing functional training using computer technology, methods of mathematical statistics. Results: is defined integrated quantitative value of the level functional of preparedness and her individual components using new methodical approaches. Conclusions: it is shown that the conduct of the optimization functional of preparedness athletes is an important factor in enhancing the effectiveness of the training process.